Here, There, or Everywhere? The Multi-Platform Practices of Creative Freelancers in Sweden - Daniel Karlsson (Nordic Journal of Working Life Studies)
This article analyzes the cross-platform and multiple-income strategies by which Swedish creative freelancers make a living in the platform economy. Through qualitative interviews and digital ethnography, the article explores how they use and interconnect a variety of platforms to manage precarious careers and piece together patchworks of income from platform-mediated gigs and non-waged income sources. The results show how creative workers manage their dependence on everchanging platforms and algorithms by diversifying their online presence and building personal ecologies of interconnected platforms to spread risk, retain autonomy vis-à-vis platforms, and stabilize incomes. It is argued that while creative workers use multi-platform practices as strategies for dealing with systematic uncertainty, these practices are also increasingly imposed as necessary in environments where creative labor is being mediated through platforms.